Labor Market Regulations in Low-, Middle- and High-Income Countries : A New Panel Database - Schindler, Martin (IMF Working Papers; Working Paper, 2011)
This paper documents a new database of labor market regulations during 1980-2005 in 91 countries, including low-, middle- and high-income countries, and contains information on unemployment insurance systems, minimum wage regulations, and employment protection legislation. In this paper, we provide details regarding the data, methodology and sources. Descriptive statistics indicate that there exists substantial heterogeneity in labor market institutions across regions and income groupings, and that much of the sample variation is driven by institutional changes over time in low- and middle-income countries. All indicators are at an annual frequency, allowing for the dating of major changes in regulation, and are based on data from a variety of sources, including the ILO, OECD and national agencies.